1981
DOI: 10.1111/j.1476-5381.1981.tb08732.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Opiate Mydriasis in Mice

Abstract: I Morphine-induced mydriasis in mice is antagonized by nalorphine, levallorphan and naloxone in a dose-dependent manner. 2 The relative potency of the three agents is 10: 56: 134 respectively, thus being in accordance with other tests of narcotic antagonism. Naloxone has the shortest duration of action. 3 When injected into naive animals, nalorphine (but not levallorphan or naloxone) produces a slight mydriasis. 4 Measurement of the diameter of the pupil in mice seems to be a precise, simple and rapid test for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…As alluded to before, some investigators believe that opioids also have a peripheral mechanism of action (Nomof, Elliot and Parker, 1968;Drago et al, 1980). Mydriasis also appears to be a speci®c opioid effect as it can be antagonized by naloxone (Klemfuss et al, 1979;Korczyn and Rock, 1981). The mydriasis caused by morphine is thought to be due both to a central mechanism of action (Oldendorf et al, 1972) and to a direct action on the iris (Korczyn and Maor, 1982).…”
Section: Fig 4 (A)mentioning
confidence: 94%
“…As alluded to before, some investigators believe that opioids also have a peripheral mechanism of action (Nomof, Elliot and Parker, 1968;Drago et al, 1980). Mydriasis also appears to be a speci®c opioid effect as it can be antagonized by naloxone (Klemfuss et al, 1979;Korczyn and Rock, 1981). The mydriasis caused by morphine is thought to be due both to a central mechanism of action (Oldendorf et al, 1972) and to a direct action on the iris (Korczyn and Maor, 1982).…”
Section: Fig 4 (A)mentioning
confidence: 94%
“…We have previously shown that this is primarily a central effect [Korczyn and Maor, 1981], easily antagonized by naloxone [Korczyn and Rock, 1981], Enkephalins can also cause naloxone-sensitive mydriasis , It was also demon strated that tolerance develops to the pupil- Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…In several species, how ever, opiates cause mydriasis [Klemfuss et al, 1978;Korczyn et al, 1979;Murray et al. 1983], The pupillary effects of opiates are thought to be of central origin [Lee and Wang, 1975;Korczyn and Maor, 1981;Murray et al, 1983], Morphine mydriasis is naloxone-reversible [Korczyn and Rock, 1981], Enkephalins also cause naloxone-sen sitive mydriasis prob ably by acting on opiate receptors in the brain.…”
Section: Introductionmentioning
confidence: 99%